Implementation of Educational Management in Improving the Quality of Education at Al-Fitri Islamic Boarding School - Siti Eva Fatimah; Andri Hendrawan ; Anwarudin Anwarudin (AIM: Journal of Islamic Education Management, 2025)
The quality of education is a critical determinant of national progress and societal welfare. Islamic boarding schools (pesantren) in Indonesia face unique challenges in managing educational quality due to limited resources and traditional institutional structures. This study aims to analyze the implementation of educational management—planning, organizing, actuating, and controlling—in improving the quality of education at Al-Fitri Islamic Boarding School, Bandung Regency, West Java. A qualitative approach with a case study design was employed. Data were collected through in-depth semi-structured interviews with the principal, curriculum coordinator, teachers, and treasurer; participant observation of teaching-learning activities, extracurricular programs, and school-community relations; and documentation analysis including school profiles, vision-mission statements, organizational structures, lesson plans, and financial records. Data analysis followed the Miles, Huberman, and Saldaña interactive model (data reduction, data display, and conclusion drawing/verification). Findings reveal that Al-Fitri Islamic Boarding School has implemented educational management fairly well across three key stages. First, planning is conducted at the beginning of each semester, encompassing objectives setting, material and learning process planning, infrastructure planning, student recruitment through written and oral tests, teacher assignment based on competence, and financial planning (RAB) allocating 35% for educational development, 20% for infrastructure, 20% for teacher consumption, and 25% for salaries. Second, implementation includes teacher competency development through workshops and seminars, learning activities guided by structured schedules and lesson plans, superior programs (tahfidz al-Qur'an, hadith memorization, dauroh tafaqquh fiddin, classical book reading, career guidance), student talent development through extracurricular activities (futsal, scouts, soccer, volleyball, martial arts), and community relations through daily lectures and monthly religious gatherings. Third, evaluation is conducted quarterly through teacher performance assessment, student learning evaluation (mid-semester tests, final semester assessments, practical exams), constructive feedback mechanisms, and recommendation formulation for program improvement. Major constraints include limited library facilities (mitigated by using WiFi and infocus for literacy), insufficient sports equipment, and financial limitations preventing participation in some competitions. This study concludes that systematic educational management—when implemented consistently with stakeholder commitment—significantly contributes to improving educational quality in pesantren. Theoretical implications affirm the applicability of classical management functions in Islamic educational institutions. Practical recommendations include improving library facilities, expanding community fundraising networks to address financial constraints, and enhancing teacher professional development programs